(3GdLeGfGJs - (3GdSdWj , CHh HcQ Hf Jbj GdOjf GdOeTbj, eMjj GdOjf,J (B1103 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3ajbhd deG cGfJ SfI KdGK heGFI hCda hfaO GdNOjf ajgG hGdEda fYH ZQGH GdHjf hJTJJ GdTed HGdGjf agj Cj gPg GdQSGdI YdGeI efHFI HGdEbGdI adgPG CSejJgG HeG ajgG s
(3BNQgG (B:s
(3hKe LeGfGJ SNajGJ hdG JNdh ef CdaGX TfjYGJ ebQaGJ, dGMJjGL eG jbY aj GdChbGJ hQHeG SfYjO GdfXQ aj GdMGdjf hGdMeO ddg hcai, hUdi Gddg hSde Ydi fHjg GdeUWai s
(3JMJhj Ydi BOGH THjgI HGdebGeGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B60s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B235 s
Keywords: (3GdCOHs